(untitled) (Mustansiria Dental Journal, 2025)
Aim: The objective of this study was to determine chronic myeloid leukemia effects on oral health status as well as presence of oral lesions in a group of Iraqi patients in comparison to healthy controls. Materials and Methods: The total sample was consisting of (60) individuals, (30) were diagnosed with (CML) and (30) were healthy controls. Clinical examination was carried out according to oral health surveys of WHO. The scoring of dental plaque was according to plaque index criteria of Silness and Löe (1964), the scoring of dental calculus was according to calculus index criteria of Ramfjord (1959), the scoring of gingival status was according to gingival index criteria of Loe and Silness (1963), probing pocket depth and clinical attachment loss were scored according to WHO oral health survey (2013) and oral lesions examination was including inspection of intra-oral soft tissues. A mouth mirror and CPI probe were used in clinical examination. Results: Plaque index, gingival index, probing pocket depth and clinical attachment loss were higher in (CML) group in comparison to healthy individuals, the difference was statistically significant (p<0.05), while it was higher in calculus index but the difference didn’t reach statistically significant difference (p>0.05). Conclusion: Patients with chronic myeloid leukemia had worse oral health condition as well as more oral lesions in comparison to healthy individuals.